AN ERROR ANALYSIS ON THE USE OF SIMPLE PAST TENSE IN STUDENTS’ WORKSHEET OF NURSING SCIENCE STUDENTS AT STIK BINA HUSADA PALEMBANG - Agus Wahyudi (Language and Education Journal, 2019)
This study was conducted to identify the kinds of errors in surface strategy taxonomy which had been done in several stages: preparation was made by reading the theory and the previous related studies. The theory was used to explain how to analyze the use of simple past tense by students on Nursing Science students’ worksheet of STIK Bina Husada Palembang. The data were taken from the third semester of English students' worksheet. The stages of analyzing the data were by identification of error, classification, description, and correction. The result of this study showed that there were three kindsof the error made by the students, such as omission, misinformation,and misordering. According to Lyons (1968, p. 54) in learning English, one of the biggest problems faced by students is grammar. In the second language learning process, a language learner cannot be separated from language errors